The Effect of Organizational Commitment and Employee Engagement on Employee Digital Readiness in Scaffolding Organizations in Greater Jakarta - Yehezkiel Panangian Sitorus; Nidya Dudija, (International Journal of Scientific Research and Management (IJSRM), 2025)
In the Industry 4.0 era, scaffolding organizations in Jabodetabek face technological transformation challenges, necessitating robust digital readiness among employees, driven by organizational commitment and employee engagement. This quantitative study, employing a descriptive and causal approach, analyzes these factors using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) on data from 163 respondents, sampled via the Hair method from an indeterminate population of scaffolding firms. Questionnaires with 49 items assessed the variables, revealing strong employee engagement (81.41%), high organizational commitment (88.24%), and ready digital readiness (78.31%), with both commitment and engagement significantly influencing digital readiness (66.6% variance explained). These findings suggest that leaders should prioritize fostering commitment and engagement to enhance digital transformation readiness, offering practical insights for scaffolding organizations to navigate Industry 4.0 competitiveness.